2012
DOI: 10.1042/an20120006
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor 1 Protects Hypoxic Astrocytes against Glutamate Toxicity

Abstract: Stroke is a major neurological disorder characterized by an increase in the Glu (glutamate) concentration resulting in excitotoxicity and eventually cellular damage and death in the brain. HIF-1 (hypoxia-inducible factor-1), a transcription factor, plays an important protective role in promoting cellular adaptation to hypoxic conditions. It is known that HIF-1α, the regulatable subunit of HIF-1, is expressed by astrocytes under severe ischaemia. However, the effect of HIF-1 on astrocytes following Glu toxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 56 publications
1
28
0
Order By: Relevance
“…GSH has been reported to protect astrocytes against various insults (Badawi et al 2012; Kim et al 2003; Scheiber and Dringen 2013). Herein, we demonstrate that IL-1β exposure renders mouse astrocytes more resistant to toxic insult mediated by the organic hydroperoxide, tBOOH, and by FeSO 4 (Figure 7), most likely by eliminating the enhanced ROS production that follows their exposure (shown directly for tBOOH in Figure 9).…”
Section: Discussionmentioning
confidence: 99%
“…GSH has been reported to protect astrocytes against various insults (Badawi et al 2012; Kim et al 2003; Scheiber and Dringen 2013). Herein, we demonstrate that IL-1β exposure renders mouse astrocytes more resistant to toxic insult mediated by the organic hydroperoxide, tBOOH, and by FeSO 4 (Figure 7), most likely by eliminating the enhanced ROS production that follows their exposure (shown directly for tBOOH in Figure 9).…”
Section: Discussionmentioning
confidence: 99%
“…31 HIF-1α has been shown to have a key role in brain edema formation and BBB disruption via a molecular pathway involving MMP-9 in brain trauma, but this is the first report to link the two in chronic vascular disease. 16 Previous investigations have showed that hypoxia-induced MMP-9 expression leads to vascular leakage, which could be reduced by MMP inhibition; in mice exposed to hypoxia, the resulting edema formation was mediated by MMP-9-dependent tight junction rearrangement, which was blocked with an MMP-9 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…When HIF‐1α stabilization is inhibited before exposure to a hypoxic stress, astrocytes suffer increased cell death due to glutamate toxicity (Badawi et al . ). Conversely, upregulation of HIF‐1α is associated with protection from ischaemia–reperfusion injury in astrocytes (Du et al .…”
Section: Protective Effects Of Prolyl Hydroxylases (Artificial Hypoximentioning
confidence: 97%